Tuberculosis arthritis and tenosynovitis - Pattamapaspong N. (2014)
The incidence of extrapulmonary tuberculosis (TB) has been rising due to the increasing number of immunosuppressed patients. Musculoskeletal system accounts for 25% of extrapulmonary TB. Most of the musculoskeletal TB involves the spine. TB of peripheral joints and tendons occur infrequently, but if untreated, it can cause serious joint and tendon destruction as well as spread of the infection to the surrounding bursa, muscle, and other soft tissues. The diagnosis of TB of joints and tendons is difficult due to the nonspecific clinical manifestations and imaging features. Concurrent active pulmonary TB is present in <50% of the patients. A positive chest radiographic finding or a positive tuberculin test supports the diagnosis, but negative results do not exclude diagnosis. Although imaging features of TB of joints and tendons are nonspecific, certain findings such as relatively preserved joint space, juxta-articular osteoporosis, cold abscesses, para-articular soft tissue calcification, and rice bodies are suggestive of TB infection. Familiarity with these imaging features can help in making an early diagnosis and facilitating proper management. © 2011 Thieme Medical Publishers, Inc.